Optimizing Procurement and Maintenance of Office Facilities to Drive Organizational Excellence - Septiana Sri Lestari; Ismiyati Ismiyati; Mar'atus Sholikah (Universitas Negeri Surabaya, 2025)
Effective procurement and maintenance practices play an important role in the success of an organization and have a direct effect on organizational performance. However, many organizations still find it difficult to optimize these practices. This study aims to examine more deeply the optimization of procurement and maintenance management of office facilities and infrastructure in Nguter Sub-district. The qualitative method is employed in this research to provide a deeper understanding of the research objectives. In collecting data, this study used direct and structured interviews with four important informants at the Nguter Sub-district Office. Data validity techniques use triangulation, and data analysis techniques include data collection, data condensation, data display, and verification. The findings of this study reveal that the practice of procurement and maintenance of facilities and infrastructure in Nguter Sub-district has run according to procedures. In procurement practices, Nguter Sub-district has implemented three methods, namely purchase, rental, and repair. Meanwhile, maintenance of office facilities and infrastructure is carried out by routine, preventive and repressive maintenance. The procurement and maintenance budgets come from APBD funds. The integration of good and optimal procurement and maintenance practices had a positive impact on improving organisational performance.